Effectiveness Of Ginger Transdermal Patch (Koyo Jahe) On Reducing The Intensity Of Labor Pain In Pregnant Women During The First Active Phase At TPMB K.B Pasuruan - Kurnia Dini Rahayu; Lailatul Nujulah; Rossalia Putri (Wahana, 2024)
One consequence of labor is pain, which can increase blood pressure, fetal heart rate, and maternal concentration. Mothers who are about to give birth can experience pain and discomfort due to uterine contractions, which begin the labor process. In most cases, pregnant women will experience pain during the labor process. Handling and monitoring labor pain during labor is very important because it determines whether pregnant women can go into labornormally or through medical procedures. Nonpharmacological methods can help reduce pain during labor. The purpose of this study is to determine the effectiveness of ginger transdermal patch (koyo ginger) to reduce the intensity of labor pain in pregnant women during the first active phase at TPMB Mrs. K.B Pasuruan. This study uses the quantitative method of Quasy Experiment, with the design of one group pretest-posttest. Koyo ginger is attached to the area of the mother's body that is in pain. Before and after 20-30 minutes of gluing, the intensity of pain is measured. The respondents of this study are mothers in the active labor phase. The analysis test uses the Wilcoxon test. The results of the analysis showed that there was a difference in the intensity of labor pain in pregnant women during the first active phase before and after the administration of koyo ginger decreased, with a sig value of 0.000 < 0.05. Most women who are about to give birth need labor pain treatment, both pharmacological and non-pharmacological treatment. Ginger is one of the nonpharmacological methods to reduce labor pain. The content in ginger can interact with pain receptors, helping relaxation, so that the mother feels more relaxed and comfortable during the delivery process